The Effect of Financial Behavior Income and Financial Knowledge on Financial Satisfaction in UMKM in Lamongan City - Wilda Fajriyah; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2022)
The background in this study is behavior of finansial management in Lamongan UMKM tends to be less good. Which is influence by several factors, namely finansial behavior, income, and finansial knowladge. This study aims to test the Financial Behavior, Income, and Financial Knowledge on Financial Satisfaction UMKM in Lamongan City. This study uses quantitative methods. The population in this study amounted to 67, while the sampling used Probability Sampling technique using Non Probability sampling. The reason is because the population is below 100, so all are taken. The samples studied by the researchers were 67 UMKM in Lamongan City. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For test tools using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that financial behavior has a positive and significant effect on financial satisfaction, income has a positive and significant effect on financial satisfaction, and financial knowledge has a positive and significant effect on financial satisfaction.